DEVELOPMENT AND CHARACTERISATION OF 3D SOLID TUMOUR CELL MODELS FOR INDIVIDUALIZED CANCER TREATMENT - A. B. Danilova; T. L. Nekhaeva; N. A. Efremova; M. A. Maydin; E. I. Fedoros; I. A. Baldueva (Сибирский онкологический журнал)
Background. To solve the problems of personalized medicine in oncology, preclinical studies based on the use of three-dimensional cellular models of tumors in vitro, including spheroids / tumoroids, are of great importance. They are an interesting tool for genetic, epigenetic, biomedical and pharmacological studies aiming to determine the most effective individual therapeutic approaches, since they allow modeling the dynamic evolution of a tumor disease from early stages to metastatic spread through interaction with the microenvironment.The purpose of the study was to compare characteristic features of formation and spatial organization of spheroids, obtained from solid malignant tumors cells with various histogenesis: melanomas, soft tissue sarcomas and osteosarcomas, epithelial tumors.Material and Methods. Solid tumor cell lines of patients who were treated from 2015 to 2021 were the basis for the creation of 3D-cell models. Fragments of tumor tissue were obtained intraoperatively: 15 samples of melanoma, 20 samples of soft tissue sarcomas and osteosarcomas, and 9 samples of epithelial tumors. All tumor cells were cultured for at least 10 passages. Methods of phase contrast, confocal microscopy, and histological techniques were used to study spheroids. Using ELISA methods and multiplex analysis, the supernatants of monolayer cell cultures and spheroids were studied for the presence of a wide range of biologically active substances that provide the processes of immunosuppression, invasion and metastasis.Results. The use of low adhesion surfaces was proven to be preferable to obtain spheroids of a given seed concentration and size of interest. The average cultivation time of spheroids was 4.7 days, and the optimal seeding concentration was 10,000 cells per well, while the spheroid diameter varied from 300 to 1000 μm depending on the type of malignant cells: the largest spheroids formed melanoma cultures. In general, the efficiency of spheroid formation was 88.6 % (39 out of 44). The introduction of fibroblasts into the 3D construct led to increasing in the invasive potential of tumor cells, which was associated with the production of IL8 (rho=0.636, p=0.035), HGF (rho=0.850, p=0.004), SCF (rho=0.857, p=0.014), FST (rho=0.685, p=0.029), Prolactin (rho=0.810, p=0.015), PECAM1 (rho=0.788, p=0.004).Conclusion. The technology of low-adhesive surfaces makes it possible to successfully create three-dimensional models of a tumor node from malignant tumors cells of various histogenesis. The colonization of a three-dimensional structure with fibroblasts enhances the biologically aggressive properties of tumor cells and demonstrates complex reciprocal interactions between the cellular elements of the tumor stroma and malignant cells, which brings the model closer to a real clinical situation.